Are cigarette smoking, alcohol consumption and hypercholesterolemia risk factors for clinical benign prostatic hyperplasia? - (:unkn) unknown (My University, 2006)
Objective: Benign prostatic hyperplasia (BPH) a histopathological term, indicates the benign morphological enlargement of the prostate gland. Clinical BPH refers to the presence of lower urinary tract symptoms (LUTS) and BPH in men. Clinical BPH is a common disease of the elderly male population with an incidence reaching nearly % 70 after the age of 60 years. Different studies have been performed to identify the risk factors for clinical BPH including age, obesity, hypertension, diabetes, vasectomy, sexual activity, physical activity, alcohol consumption, cigarette smoking, caffeine consumption, hormonal status and hyperlipidemia. However, the potential role of the afore-mentioned risk factors in the pathogenesis of clinical BPH is not clarified yet. In this study we investigated whether certain risk factors such as hypercholesterolemia, cigarette smoking and alcohol consumption play a role in the occurrence of clinical BPH. Methods: Between 1997 and 2000 a total of 142 patients admitted to the outpatient clinic with lower urinary tract symptoms (LUTS) were included in this prospective study. The International Prostate Symptom Score (IPSS) was administered to all patients by the primary physician and history of cigarette smoking and alcohol consumption was noted. On the day of examination, fasting blood samples were collected for serum cholesterol and PSA. All patients underwent uroflowmetric analysis. Patients with benign prostatic enlargement in digital rectal examination and with an IPSS>7 and a maximum flow rate < 10 ml/sec were considered as having clinical BPH. The results were analysed by student t test, Chi square test or ANOVA where appropriate. Results: Ninety-seven (%68.3) patients were found to have clinical BPH whereas 45 (31.7%) patients were not diagnosed as clinical BPH. The mean serum cholesterol level of the patients with and without clinical BPH was 226 mg/dl and 224 mg/dl, respectively (p<0.05). Thirty-four (35.1%) patients with clinical BPH were regular smokers whereas 25 (55.6%) patients without BPH were smokers (p=0.047). The ratio for alcohol consumption was 6% in clinical BPH patients and 13.3% of the patients without clinical BPH (p=0.041). According to PSA values, 23 (23.8%) patients who had clinical BPH had PSA<4ng/ml whereas 7 (15.6%) patients without clinical BPH had PSA>4ng/ml (p>0.05). Conclusion: Our results indicate a protective effect of cigarette smoking and alcohol consumption in the occurrence of clinical BPH whereas serum cholesterol and PSA levels did not reveal a significant effect on the occurrence of clinical BPH.
Keywords: Alcohol; Cholesterol; Cigarette; Prostate hyperplasia